Selection of The Best Location for Opening A Branch Office: A Case Study on Bank X - Sugiyanto Sugiyanto; Akhmad Yunani; Lely Savitri Dewi; M. Arsyad Arradya S.P. (Operations Excellence: Journal of Applied Industrial Engineering, 2023)
Branch offices for a bank have a strategic role to build closeness with customers and improve service quality. Determining a branch’s location is an important decision that must consider various criteria. A branch office of Bank X faces problems related to the condition of the branch office, in addition to the traffic jam is also the narrowness of the available parking lots. This study aims to conduct an alternative location ranking study to obtain the best location for the relocation of the branch office. The analysis was carried out qualitatively and quantitatively, by implementing the Analytic Hierarchy Process (AHP) for alternative locations by considering various aspects. Focus Group Discussion (FGD) and observation were undertaken to collect data. There are three alternative locations that can be selected for the relocation of the branch office. Applying the AHP shows that Jl. Raya P3 is the best location for the relocation of Bank X Branch Office. To relocate the branch office, a comprehensive study is needed in the form of a feasibility study for the selected and due diligence location with the manager during the land acquisition process so that it is clear and clean.